In Ornamental Crops... Empowering farmers and breeders for their rights - Prasad, K. V.; Janakiram, T. (Indian Horticulture, 2019)
The breeders across the world market their creations either directly or through their authorized delaers to ensure the compliance of plant breeders’ rights. The breeders monitor the number of flowers that reach the international markets from a particular producer as they are aware of the production potential of a particular variety. Once the potential exceeds beyond a limit it becoems obvious that the extra production is imperatively coming from illegally propagated material. The reprecussion of illegal propagation include confiscation of the consignments, destruction of entire batch of consignments and levying of charges for such disposal beside loss of reputation in the markets. The growers in general and the consumers in particular in countries without enforceable breeders’ rights protection are at a disadvantage as a number of breeders are likely to avoid sharing their latest and best creations into that market. Royalties collected over the plant material fuels further product development and would motivate a breeder to continuously make improvements. Growers in countries that do not have breeders’ rights still have to pay royalties on protected varieties if the products they are selling are protected in the final destination.